2019
DOI: 10.1002/jcb.29387
|View full text |Cite
|
Sign up to set email alerts
|

miR‐200c overexpression inhibits the invasion and tumorigenicity of epithelial ovarian cancer cells by suppressing lncRNA HOTAIR in mice

Abstract: Epithelial ovarian cancer (EOC) is a common ovarian cancer in gynecological cancers today. It has been found that microRNAs and long‐chain noncoding RNA (lncRNA) regulate the gene transcriptional expression in cells. However, it is not well understood that the upstream and downstream regulatory molecules of lncRNA HOX antisense intergenic RNA (HOTAIR). The effects of miR‐200c overexpression on the invasion and nude mouse tumorigenicity, as well as lncRNA HOTAIR and snail expression of EOC SKOV3 cells, should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…The axis HOTAIR/miR-200c/SNAIL (or SNAI1, zinc finger transcription factor), involved in OvCa invasion, was demonstrated using transduced lentivirus-miR-200c, gain-or loss-of-function assays, EMT markers, and tumorigenicity of SKOV3 cells in xenograft tumor studies [118]. In recent work, it was shown that miR-138-5p could directly bind to HOTAIR and 3 -UTR of EZH2 (enhancer of zeste homolog 2, a histone-lysine N-methyltransferase) and SIRT1 (NAD-dependent deacetylase sirtuin 1), which was validated by the dual-luciferase reporter assay [119].…”
Section: Oncogenic Lncrnas As Cernas In Ovarian Cancermentioning
confidence: 99%
“…The axis HOTAIR/miR-200c/SNAIL (or SNAI1, zinc finger transcription factor), involved in OvCa invasion, was demonstrated using transduced lentivirus-miR-200c, gain-or loss-of-function assays, EMT markers, and tumorigenicity of SKOV3 cells in xenograft tumor studies [118]. In recent work, it was shown that miR-138-5p could directly bind to HOTAIR and 3 -UTR of EZH2 (enhancer of zeste homolog 2, a histone-lysine N-methyltransferase) and SIRT1 (NAD-dependent deacetylase sirtuin 1), which was validated by the dual-luciferase reporter assay [119].…”
Section: Oncogenic Lncrnas As Cernas In Ovarian Cancermentioning
confidence: 99%
“…Abnormal expression of long non-coding RNAs (lncRNAs) and microRNAs (miRNAs/miRs) has been demonstrated to be related to tumor formation and progression in various types of cancers (10)(11)(12). For example, lncRNA HOTAIR was found to be suppressed in ovarian cancer cells, which was found to inhibit the invasion and tumorigenicity by interacting with miR-200c in mice (11). lncRNA MIR4435-2HG was found to promote prostate cancer migration and invasion by upregulating TGF-β1 expression (10).…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a diverse class of RNA transcripts longer than 200 nucleotides that have limited protein coding capacity (7,8). lncRNAs have been found to participate in various biological processes in cancers such as cervical cancer, prostate carcinoma, epithelial ovarian cancer and breast cancer, including tumorigenesis, metastasis and chemotherapy resistance (9)(10)(11)(12). Recent evidence shows that lncRNAs play oncogenic or tumor-suppressor roles in OSCC (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of EMT-related genes and specific matrix metalloproteinases (MMPs) by HOTAIR is believed to be responsible for OC metastasis [ 117 , 118 ]. Moreover, the hyper-expression of HOTAIR is also co-related with specific miRNAs expressions [ 119 ]. For instance, HOTAIR upholds the OC stem cells stemness by upregulating a protein-coding gene TBX3 through the miR-206/TBX3 axis [ 120 ].…”
Section: Lncrnas In Female-oriented Cancersmentioning
confidence: 99%